An annotated bibliography and analysis of coaching science - Gilbert, W. D. (2002)
The purpose of this project was to prepare an annotated bibliography and analysis of the published research on coaching science. In an effort to understand and improve coaching techniques that foster enjoyment, skill development, and personal growth and development for sport participants, researchers have studied coaches for over a quarter of a century (Trudel & Gilbert, 1995). However, a systematic and comprehensive analysis of the scientific inquiry into coaching has yet to be completed. The absence of a guiding framework seriously limits the ability of (a) researchers to set research agendas, (b) coaches to access and realize the potential of coaching research, and (c) coach educators to integrate the full scope of coaching research into the development of coach training programs. As a result, coaching science has been criticized both for its lack of impact on coaching practice (Abraham & Collins, 1998) and for its lack of organization (Potrac, Brewer, Jones, Armour, & Hoff, 2000). The project design is based on a similar analysis of research on teaching in physical education (Silverman & Skonie, 1997). The project followed a three-phase design. In Phase I an exhaustive search, using computerized databases and encyclopedias, was conducted for all English language coaching research published in scientific periodicals between 1970 and 2001. The objective of Phase II was to obtain copies of all the published research identified in Phase I. An analysis of the published research was completed in Phase III. A categorizing system and a coding matrix was developed following guidelines used in similar projects (e.g., Culver, Gilbert, Trudel, in press; Silverman & Skonie, 1997). The following information was coded for each article: (a) author names, (b) year of publication, (c) publication outlet, (d) coaching focus, (e) research approach, (d) methods of data collection, (f) type of participants, and (g) sample demographics - number and gender of coach participants, level of competition, type of sport, and sampling criteria. Over 1,100 articles were reviewed and 611 met the criteria for inclusion in the bibliography. A summary of the data, and trends in coaching science, is provided. The annotated bibliography and analysis will provide a critical source of information to help bridge the theory-practice gap (Abraham & Collins, 1998; Haag, 1994) and to develop a conceptual framework for coaching science (Potrac et al., 2000). Researchers and practitioners alike will benefit from a single resource that compiles and analyzes the research on coaching science.